Vitamin D supplementation at 4000 IU/d does not alter speed and power in female footballers at international level - Michalczyk, M. M.; Gepfert, M.; Zydek, G.; Gawelczyk, M.; Osowski, M.; Golas, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
Vitamin D plays an important role in neuromuscular function. Its active form, calcitriol, supports the nervous and muscular systems by regulating calcium levels in the body. Calcium is an essential ion involved in nerve impulse transmission and muscle contraction. Vitamin D deficiency can impair neuromuscular conduction, leading to muscle weakness, reduced contractile force and, in severe cases, muscle cramps or tremors. Recent studies suggest that many athletes are vitamin D deficient. The aim of this study was to assess the effect of eight weeks of vitamin D3 supplementation on speed and muscular strength in professional female footballers. Female football players (n=23) at international level (tier 4) were divided into two groups and given either vitamin D at a dose of 4,000 IU/day (n=12) or a placebo (n=11). Four players withdrew from the study. The study was conducted during the preparatory phase. The study was conducted during the preparatory phase. All participants completed an anaerobic endurance test (RAST) and speed tests over 5 m and 30 m both before and after the intervention. A multi criterial repeated measures ANOVA showed no significant interactions for 25(OH)D3 levels in blood (p=0.47), 5m (p=0.34) and 30m (p=0.48) speed test, RAST (p=0.94) and peak power (p=0.066). Nor main effects of group on blood 25(OH)D3 levels (p=0.29), 5 m (p=0.46) and 30 m (p=0.48) speed test and peak power (p=0.067). There were also no main effects of time on blood 25(OH)D3 levels (p=0.33), 5 m speed test (p=0.24) and peak power (p=0.084). However, there were main effects of time on 30 m speed test (p=0.0052) and RAST (p=0.001) and main effects of group on RAST (p=0.04). Changes in the main effect of group on RAST and the main effect of time on RAST and the 30 m speed test were due to the effect of training. Vitamin D supplementation had no significant effect on lower limb strength in female footballers. In conclusion, the lack of significant changes in blood 25(OH)D3 levels between the supplemented and placebo groups suggests that a dose of 4,000 IU/day may not be sufficient for athletes to improve their anaerobic capacity. Given the high utilisation of vitamin D3 during and after exercise, these results suggest that a higher dose of supplementation may be required to achieve optimal results.